Space exploration. ([Ipswich, MA] : EBSCO Information Services ; Amenia, NY : Grey House Publishing, 2025)
Looks at the state of space exploration in the 21st century and explores a variety of views about how space science and exploration could and should evolve in the future.
A Self-Declared Space Nation Called Asgardia Is Planning a Fully -- Functioning Space Economy and Wants Help from Elon Musk and Jeff Bezos -- Is There a Place for Spirituality in Space Science? -- Space Nation Issues Declaration of Independence -- The Uber-Optimistic History and Prolonged Future of Space Tourism: Popular Science Predicted Luxury Space Vacations by 2007 -- "Who Gets to Leave the Earth?" -- To Mars and Beyond -- Martians and Exoplanets -- So You Want to Be a Space Farmer -- Space Tech: Experts Name 12 Transformative Technologies Reshaping Our Cosmic Future -- Can the Human Body Endure a Voyage to Mars? -- How a Scientist and Cartoonist Envision Living on the Moon and Mars -- Technology Tested in Space Is Preparing Us for the Moon and Mars -- Bibliography -- Websites -- Index.
H.W. Wilson.
Includes bibliographical references and index.
10-A.
Keywords: Astronautics; Astronautics and civilization; Manned space flight; Astronautics; Astronautics and civilization; Space flight; Outer space -- Exploration; Outer space -- Exploration